Macroeconomic Influences on Baltic Housing Loan Flows - Stasiulionytė, Mija Aneta (Vilnius University Open Series, 2024)
This study investigates the impact of macroeconomic factors on housing loan flows in the Baltic region post-2008 housing bubble. Using stepwise regression, Lasso regression, and pooled regression, data is analyzed from Estonia, Latvia, and Lithuania spanning 2014 to 2023. Results reveal the significant influence of borrowing costs, wages, unemployment, and inflation rates on loan flows.